Using Real-Time Adherence Feedback to Enhance Communication About Adherence to Antiretroviral Therapy: Patient and Clinician Perspectives. (January 2020) - Hill, Lauren M.; Golin, Carol E.; Pack, Allison; Carda-Auten, Jessica; Wallace, Deshira D.; Cherkur, Sruthi; Farel, Claire E.; Rosen, Elias P.; Gandhi, Monica; Asher Prince, Heather M.; Kashuba, Angela D. M.
Abstract: New technologies for real-time adherence monitoring hold the potential to enhance antiretroviral therapy adherence interventions by providing objective information about daily medication-taking behavior. To realize this potential, we need to understand how to integrate real-time adherence feedback into existing best practices to promote antiretroviral therapy adherence at the point of care. Using in-depth interviews with 30 HIV-infected patients and 29 HIV care clinicians, our primary aims were to understand patients' and clinicians' perceptions of anticipated benefits and preferred uses of objective feedback to enhance conversations about adherence and to identify concerns about the impact of objective monitoring on patient–clinician relationships and communication. Both patients and clinicians suggested that identifying patterns of nonadherence with real-time feedback could (a) facilitate collaborative adherence problem-solving, (b) motivate patient adherence, and (c) reinforce the importance of optimal adherence. Some clinicians worried that delivery of real-time feedback could imply mistrust of patient-reported adherence and suggested careful framing of monitoring results. A few patients and clinicians were concerned that negative reactions to monitoring could discourage retention in care and reduce adherence motivation. These results indicate the potential of real-time feedback to enhance existing evidence-based adherence interventions targeting the key adherence precursors of adherence information, motivation, and behavioral skills. Guidance for the delivery of real-time adherence feedback should focus on both optimizing adherence and mitigating negative perceptions of adherence monitoring.